Application of electrodeposition for Nickel Nanoparticle-Modified Electrodes in Biochemical Systems - Fatemeh Mahmoodzadeh; Nahid Navidjouy; Saber Alizadeh; Mostafa Rahimnejad (MethodsX)
Microbial fuel cells (MFCs) have garnered significant attention from researchers as an innovative and environmentally friendly method for the treatment of urban and industrial wastewater. The type and material of the electrode are critical factors affecting the efficiency and energy production of this process. The electrodeposition method was employed to dope nickel (Ni) and modify the surface of graphite plates (GP) and carbon felt (CF). The maximum voltage, current density, and power generated by the MFC were evaluated under consistent temperature conditions. Field-emission scanning electron microscopy (FE-SEM) results confirmed successful Ni doping and adequate microorganism attachment to the Ni-deposited electrodes, leading to enhanced electron transfer and increased power generation. Additionally, the highest average voltage output was observed using modified bio-Ni@CF (468.0 mV) and bio-Ni@GP (422.0 mV) electrodes, compared to bare CF (382.0 mV) and GP (301.0 mV) electrodes. Monitoring the open-circuit voltage (OCV) data for four loadings of the MFC with different anodes indicated the suitable resistance and stability of the Ni film over time. Therefore, the electrodeposition method can be considered a suitable technique for modifying the anode electrodes using Ni in MFCs.